Sekitar Pendirian Sampai Periode Awal MAN Insan Cendekia Padang Pariaman : Studi Sejarah Lembaga - Ray Silva; Abdul Salam (Jurusan Sejarah FIS UNP, 2023)
This study discusses the development of the Padang Pariaman Scholars MAN in 2016-2022. The research aims to determine the background of the establishment of MAN Insan Cendekia in Padang Pariaman Regency and its development in 2016-2022. This study uses historical methods consisting of historographic steps, namely heuristics, verification, interpretation and historiography. The results of this study indicate that MAN Insan Cendekia was born on the idea of ​​the Head of the Agency for the Assessment and Application of Technology (BPPT) held by Prof. Dr. ing. Bacharuddin Jusuf Habibie who wants a balance of mastery of Science and Technology for productive Muslim student generations. After being delegated its management to the Ministry of Religion of the Republic of Indonesia in 2001, over time MAN Insan Cendekia has grown to West Sumatra. The selection of Padang Pariaman Regency as the location for MAN Insan Cendekia is because the location is strategically close to government offices and international airports, the condition of the land is wide and flat, the conditions of the environment are beautiful and far from the crowds. In 2022 MAN Insan Scholar Padang Pariaman succeeded in obtaining the first position as the best school in West Sumatra and producing alumni who are spread both at home and abroad. The presence of MAN Insan Cendekia has an economic and socio-cultural impact on the surrounding community, such as providing livelihoods for local residents and repairing the road to MAN IC has a positive impact on the community.